Ethnic differences in HIV risk perceptions and behaviors among Black 18-39 year-old residents of Broward County, Florida. - Villanueva, Loreto P; Darrow, William W; Uribe, Claudia; Sánchez-Braña, Elizabeth; Obiaja, Kenneth; Gladwin, Hugh (AIDS education and prevention : official publication of the International Society for AIDS Education, 2010)
The study assessed ethnic differences in the perceived risks of HIV infection, sexual experiences, and HIV-antibody testing histories among Black populations in Broward County, Florida. Data were analyzed for 2,731 well-characterized survey respondents 18-39 years old who indicated they were African Americans, Caribbean Islanders, English-speaking, or Creole-speaking Haitians. Creole-speaking Haitians were least likely to consider themselves at risk of HIV infection, report using condoms in the last 12 months, and indicate that they had ever been tested for HIV. English-speaking Haitians were more likely than African Americans to report never engaging in sexual intercourse and were less likely to have ever been tested for HIV. English-speaking Caribbean Islanders reported preventive behaviors similar to those of African Americans, but had lower perceptions of HIV risk and were less likely to have ever been tested. Health promotion programs designed to improve HIV prevention practices must appreciate social and cultural differences among Black populations.
Keywords: Adolescent; Adult; African Americans; Attitude to Health; Caribbean Region; Condoms; Cultural Characteristics; Data Collection; Female; Florida; Haiti; HIV Infections; Humans; Male; Risk; Young Adult